The "whole ingredients extract" of Astragali Radix improves the symptoms of dextran sulfate sodium-induced ulcerative colitis in mice through systemic immunomodulation - Ke-Gang Linghu; Qiushuo Ma; Shi-Hang Xiong; Mingming Zhao; Qiling Chen; Wen Xu; Meiwan Chen; Jian-Ye Zhang; Yuanjia Hu; Wei Xu; Hua Yu (BMC, 2022)
Abstract Background Ulcerative colitis (UC) is a common inflammatory intestinal disease. Astragali Radix (AR) is one of the traditional Chinese medicines used in clinic for UC treatment. In our previous study, the whole ingredient extract (WIE) from AR have been proved to possess better immunomodulatory effects on immunosuppressed mice compared with the conventional water extraction (WAE). In the present study, we further evaluated the therapeutic effects of WIE against dextran sodium sulfate (DSS)-induced UC in mice through systemic immune regulation. Methods Gradient solvent extraction has been used to prepare the WIE of AR. The HPLC-MS analysis approach has been employed to analyze and compare the chemical differences between WAE and WIE. UC model was reproduced in 3% DSS-induced C57BL/6 mice for 6 days. Flow cytometric analysis for splenic lymphocyte subset. ELISA kits were used to determine the cytokines in the serum and colon tissues. The histopathological characteristics of colon were evaluated by hematoxylin-eosin staining and immunohistochemistry. Results The chemical compositions and the contents of main active ingredients were more abundant and higher in WIE than those in WAE. The WIE treatment altered a better action on reducing colitis disease activity index (DAI) and histological scores, as well as the recovered body weight and increased colon length in mice compared to the WAE group. Additionally, WIE showed better effects in recovering the levels of peripheral white blood cells in blood and cytokines (IL-2, IL-6 and MCP-1) in serum or colon tissues, improving the percentage of CD3+ and the ratio of CD4+/CD8+ in the spleen, and inhibiting the spleen enlargement in DSS-induced UC mice. Conclusions WIE has a more complete chemical composition than WAE. Meanwhile, WIE possesses better therapeutic effects on UC through resuming dysfunctional immunity in mice.